Arbitration Laws and Judicial Response to Settling the Disputes Through Arbitration in Nepal - Giri, Saroj Kumar (Journal of Management, 2022)
The article aims to analyze the arbitration-related laws in Nepal, the domestication of international arbitration treaties and conventions, settlement procedures of arbitration disputes and the role of the Nepalese judiciary to settle the disputes through arbitration. To settle disputes outside the court through a mutual agreement in a peaceful situation, ADR (Alternative Dispute Resolution) is the best method practiced worldwide since time immemorial; Nepal has also proclaimed various provisions in different statutes and rules. Arbitration Act, 2055 is the current statute that governs arbitration matters and Arbitration (Court procedures) Rule, 2059 governs the court proceedings. The various provisions of Arbitration Laws and Rules have been proclaimed to mitigate the international arbitration laws and rules. Nepalese judiciary especially the supreme court and high court has played a pivotal role to settle the dispute that arose during arbitration, arbitral award, its implementation, the appointment of arbitrator etc. The finding of the study is there have been significant changes in the decision-making process by the court and new trends mitigating the international proceedings have been followed. The analysis is significant as it helps to understand the arbitration laws and procedures and new trends adopted by the courts to settle disputes.